Gamification in Open Design: Supporting the Choice of Context-Appropriate Gamification Elements - Fedechen, Emerson André; Silva Junior, Deógenes; Pereira, Roberto (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2022: Anais do XVIII Simpósio Brasileiro de Sistemas de Informação, 2022)
Context: Open Design proposes a model of collaborative and voluntary work with full and free access to information, to the construction process and to the product resulting from the work. Open Design projects are dependent on the engagement of their participants, needing approaches that support engagement. Gamification uses game elements to induce positive behavior in people promoting motivation and engagement in specific tasks. Problem: However, due to the complexity of Open Design, it is not trivial to identify which gamification elements and strategies can be successfully used to engage people. The use of gamification without observing the relationship between the elements of gamification and the Open Design context can bring unwanted results in relation to the goals of gamification. Methodology: In this article, we present the cataloging of 105 gamification elements identified in the literature and a process to support gamification in Open Design. Theory of IS: The process and catalog were built taking into account the Self Determination Theory and the 5W2H conceptual framework that supports the gamification design. The Process and Catalog were experimented in a case study with 11 participants and evaluated with a questionnaire based on the Technology Acceptance Model. Summary of Results: The results of the case study indicated the feasibility and acceptance of the catalog and process by the participants, and revealed points for improvement, especially in terms of ease of use. Contributions and Impact in the IS area: The Process and the Catalog are promising in supporting the planning of gamification in Open Design, especially in providing designers with tools to understand the context to be gamified and to select suitable gamification strategies and elements.